Vietnam Country Gender Assessment - World Bank (World Bank, Hanoi, 2017)
Viet Nam has undergone a major socio-economic transformation over the past quarter century, rising from one of the poorest countries in the world to a middle income country. Today it continues to develop rapidly, becoming more integrated with the global economy and undergoing significant regulatory and structural changes. Viet Nam has also made remarkable progress on gender equality, but important gender differences still remain. On the positive side Viet Nam has had considerable progress in addressing gender disparities in education, employment and health. The gender gap in earnings is lower in Viet Nam than in many other East Asian countries. Indeed by a number of measures, women's outcomes have improved significantly. However, upon deeper examination of the data, a number of challenges still remain. The report is organized into five chapters. The current chapter has provided a background to the report and the process through which it has been prepared. The next three chapters will deal with the substantive issues, focusing primarily on gender but addressing ethnicity and other forms of social inequality where relevant. Chapter two will provide an analysis of the situation and trends in gender equality in relation to the multiple dimensions of poverty, some of which are included in the Millennium Development Goals (MDGs). Chapter three will provide an in-depth gender analysis of livelihoods and employment, bearing in mind the likely impact of the recent crisis as well as the challenges of transition to middle income status. Chapter four will pick up on the issue of women's political participation in leadership positions and in the wider society. The final chapter will synthesize the key findings of the report and prioritize key recommendations.